Peningkatan Kompetensi Guru Melalui Lesson Study: Kasus Di Kabupaten Bantul - JM Tedjawati (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2011)
The purpose of this writing is find out about the implementation of lesson study program, especially in terms of: 1) The implementation of lesson study program, 2) The role of school principals and heads of education offices in the implementation of lesson study program, and 3) The impact of the implementation of lesson study program. It’s objective is to address the problems being faced today, to what extent the implementation of lesson study can be applied in the classroom and the impact of the lesson study program. Analysis findings show that: 1) Lesson study program can be implemented because of the support of cooperation between teachers, principals, and the role of coordinator in preparing the program. For teachers, the program is very useful in the classroom, while increasing the ability of competence. Teachers are required to be able to do lesson planning, teaching practice, as well as receive input from other teachers or facilitators, or principal, 2) The existence of support from school principals and heads of education offices in lesson study program. The role of principals, among others, support in the implementation, mentoring, and financing activities of lesson study. The role of head of educational office including the provision of training and certification for teachers, approved the use of the funds for lesson study program, and 3) The impact lesson study program for teachers is the increasing ability of teachers. They are more innovative in teaching with variety in the methods and more relevant towards student’s ability. In addition, theachers quality and quantity increase in implementing the Classroom Action Research (PTK). ABSTRAKTujuan penulisan ini dimaksudkan untuk mengetahui pelaksanaan program lesson study, khususnya dalam hal: 1) Pelaksanaan program lesson study; 2) Peran kepala sekolah dan kepala dinas pendidikan dalam pelaksanaan program lesson study; dan 3) Dampak pelaksanaan program lesson study. Temuan analisis ini menunjukkan bahwa: 1) Program lesson study dapat dilaksanakan karena adanya dukungan kerja sama antar guru, kepala sekolah, dan peran koordinator dalam menyusun program. Bagi guru, program ini sangat bermanfaat dalam pembelajaran di kelas, sekaligus dapat meningkatkan kemampuan kompetensinya. Guru dituntut untuk dapat melakukan perencanaan pembelajaran, mempraktikan pembelajaran tersebut, serta menerima masukan dari guru lain ataupun fasilitator atau kepala sekolahnya; 2) Adanya dukungan dari kepala sekolah dan kepala dinas pendidikan dalam program lesson study. Peran kepala sekolah antara lain dukungan dalam pelaksanaan, pendampingan, dan pendanaan kegiatan lesson study. Peran kepala dinas antara lain pemberian pelatihan dan sertifikat bagi guru, menyetujui penggunaan dana BOS untuk program lesson study; dan 3) Dampak program lesson studybagi guru adalah meningkatnya kemampuan guru. Mereka lebih inovatif dengan metode pembelajaran lebih bervariasi dan lebih relevan terhadap tingkat kemampuan siswa serta meningkatnya kualitas serta kuantitas guru dalam melaksanakan Penelitian Tindakan Kelas (PTK).